1991
DOI: 10.1021/bi00107a028
|View full text |Cite
|
Sign up to set email alerts
|

Structural determination of oligosaccharides derived from lipooligosaccharide of Neisseria gonorrhoeae F62 by chemical, enzymic, and two-dimensional NMR methods

Abstract: F62 LOS of Neisseria gonorrhoeae consists of two major LOS components; the higher and smaller molecular weight (MW) components were recognized by MAbs 1-1-M and 3F11 respectively. Base-line separation of the two major oligosaccharide (OS) components from F62 LOS was achieved by Bio-Gel P-4 chromatography after dephosphorylation of the OS mixture. The structures of the two major OSs were studied by chemical, enzymatic, and 2D NMR methods [double quantum filtered COSY (DQF-COSY), delayed COSY (D-COSY), homonucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

16
112
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(128 citation statements)
references
References 30 publications
(42 reference statements)
16
112
0
Order By: Relevance
“…The structure of the LOS of a few strains of GC has been published (1)(2)(3) and is summarized in Fig. 1.…”
Section: Sultlnlarymentioning
confidence: 99%
See 1 more Smart Citation
“…The structure of the LOS of a few strains of GC has been published (1)(2)(3) and is summarized in Fig. 1.…”
Section: Sultlnlarymentioning
confidence: 99%
“…Fig. 1 A shows the most complete structure that has been reported for strain F62 (1). In the smallest naturally occurring variant, the c~ chain consists ofa lactosyl group (Gal .…”
Section: Sultlnlarymentioning
confidence: 99%
“…In addition to complex LOS expression, studies by us and others (8,11) have shown that gonococci may mimic human glycolipids or may change serum sensitivity by modifying their LOS (15)(16)(17). The 4.5-kDa LOS produced by strain F62 contains a lactoneotetraose moiety that is linked to the Hep [1] residue of the core trisaccharide as described above (11).…”
mentioning
confidence: 99%
“…The 4.5-kDa LOS produced by strain F62 contains a lactoneotetraose moiety that is linked to the Hep [1] residue of the core trisaccharide as described above (11). This tetraose is the carbohydrate moiety also found in a human glycosphingolipid, paragloboside (8,11).…”
mentioning
confidence: 99%
See 1 more Smart Citation